2018
DOI: 10.1210/jc.2017-02629
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Cardiovascular Disease Among Thyroid Cancer Survivors: Findings From the Utah Cancer Survivors Study

Abstract: Our findings suggest that examining the effect of thyroid cancer diagnosis, cancer treatment, and demographic characteristics on the risk of CVD is critical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 37 publications
3
29
1
Order By: Relevance
“…It is also consistent with a study reporting a neutral effect of DTC on cardiovascular mortality and a recent study reporting comparable long‐term cardiovascular outcomes between euthyroid and hyperthyroid patients . On the other hand, our findings may be seen as complementary to those of a recent elegant study reporting several baseline factors associated with increased CVD risk among thyroid cancer survivors . Unfortunately, direct comparison of the reported CVD outcomes in this study is not feasible, because of the differences in study design, handling of the baseline CVD disease, definition of CVD outcomes and the primary research hypothesis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It is also consistent with a study reporting a neutral effect of DTC on cardiovascular mortality and a recent study reporting comparable long‐term cardiovascular outcomes between euthyroid and hyperthyroid patients . On the other hand, our findings may be seen as complementary to those of a recent elegant study reporting several baseline factors associated with increased CVD risk among thyroid cancer survivors . Unfortunately, direct comparison of the reported CVD outcomes in this study is not feasible, because of the differences in study design, handling of the baseline CVD disease, definition of CVD outcomes and the primary research hypothesis.…”
Section: Discussionsupporting
confidence: 90%
“…complementary to those of a recent elegant study reporting several baseline factors associated with increased CVD risk among thyroid cancer survivors 32. Unfortunately, direct comparison of the reported CVD outcomes in this study is not feasible, because of the differences in study design, handling of the baseline CVD disease, definition of CVD outcomes and the primary research hypothesis.…”
contrasting
confidence: 74%
“…Given the relatively young age of patients at diagnosis and a survival rate that is even better than in the general population [2], in the long term, comorbidities play a major role in the lives of survivors of thyroid cancer. Studies have identified various long-term complications in thyroid cancer survivors, including cardiovascular disease [6], and aging-related problems [7]. These comorbidities are highly attributed to lifestyle factors, emphasizing the value of positive health behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts are currently underway to try to capture more detailed information on the post-treatment experiences of cancer survivors that could inform future approaches to clinical care. In a series of studies 8,9 , Hashibe and colleagues used data linkages between a statewide cancer registry, electronic health records from major health systems, and birth, death and residential records to identify high-risk groups among survivors of thyroid cancer. By incorporating details related to treatment regimens, sociodemographic of long-term cancer survivors will require a sophisticated understanding of the interplay between cancer-related risks of morbidity as individuals age over time.…”
Section: Eden R Brauer and Patricia A Ganzmentioning
confidence: 99%
“…Current opinion favours a risk-stratified approach based on treatment intensity, wherein low-risk survivors (such as those who had breast ductal carcinoma in situ) are transitioned to primary care for follow-up care, while high-risk survivors (such as those who required allogeneic stem cell transplantation) continue to receive specialized oncology care, and the intermediate-risk group are generally managed according to a shared care model. A more detailed approach to examining cancer survivorship outcomes similar to that adopted by Hashibe et al 8,9 could provide a basis for delineating risk strata and informing appropriate care models.…”
Section: Competing Interestsmentioning
confidence: 99%